Variation of the Ribosomal Operon 16S-23S Gene Spacer Region in Representatives of Salmonella enterica Subspecies - Luz, Sara Pérez (American Society for Microbiology, 1998)
The 16S-23S spacer regions of two ribosomal operons (rrnA and rrnE) have been sequenced in seven representatives of the Salmonella enterica subspecies. Isolated nucleotide substitutions were found at the same sites as in Escherichia coli but the number of polymorphic sites was much larger, as could be expected for a more heterogeneous species. Still, as in E. coli, most of the variation found was due to insertions and/or deletions affecting blocks of nucleotides generally located at equivalent regions of the putative secondary structure for both species. Isolated polymorphic sites generated phylogenetic trees generally consistent with the subspecies structure and the accepted relationships among the subspecies. However, the sequences of rrnE put subspecies I closer to E. coli K-12 than to the other S. enterica subspecies. The distribution of polymorphisms affecting blocks of nucleotides was much more random, and the presence of equivalent sequences in distantly related subspecies, and even in E. coli, could reflect relatively frequent horizontal transfer. The smallest 16S-23S spacers in other genera of the family Enterobacteriaceae were also sequenced. As expected, the level of variation was much larger. Still, the phylogenetic tree inferred is consistent with those of 16S rRNA or housekeeping genes.